Properties Of Poly (Lactic Acid) / Polybutylene Adipate Terephthalate Reinforced With Oil Palm Empty Fruit Bunch Composites For Fused Deposition Modeling 3d Printing - Ayob, Nor Amira Izzati (2021)
Poly (lactic acid) (PLA) is amongst the preferable materials used in 3D printing because of its unique properties such as good appearance, higher transparency, less toxicity and low thermal expansion that help reduce the internal stresses caused during cooling. However, PLA is brittle and has low toughness and thermal resistance that affect its printability and restricts its industrial applications. Therefore, in this study, PLA is blending with various content of Polybutylene adipate terephthalate (PBAT) at 20, 50 and 80 wt.% in a twin-screw extruder. The tensile, thermal, morphology and rheological behaviour of PLA/PBAT filaments were characterized. Then, the most promising and balance properties of PLA/PBAT (80 wt.% PLA: 20 wt.% PBAT) was subjected to reinforced with 10 wt.% Empty Fruit Bunch (EFB) and the biodegradation of PLA/PBAT and PLA/PBAT/EFB were investigated. After that, the selected PLA/PBAT and PLA/PBAT/EFB filaments were printed using a Fused Deposition Modeling (FDM) 3D printing machine and the performance of PLA/PBAT and PLA/PBAT/EFB were compare between the 3D printing and compression moulding techniques. The physical, mechanical, thermal and morphology properties of PLA/PBAT and PLA/PBAT/EFB were characterized.